Hot shot [large type] - Michaels, Fern (Michaels, Fern. Men of the Sisterhood, 2019)
The Sisterhood is a group of women bound by friendship and a quest for justice. Now their male allies have formed a top-secret organization with the same goals. When Lizzie Fox's husband, Cosmo Cricket, is critically injured in a shooting, the men of head straight to Las Vegas to comfort Lizzie and find the assailant. As the head of Nevada's Gaming Commission, Cosmo has powerful enemies, but the shooting may be related to a private project: Happy Village, a flourishing retirement community with a complicated past. Jack, Harry, and the rest of the crew risk everything to remove the threat. And while the Men of the Sisterhood fight for justice, Cosmo is fighting for his life.